UMP collaboration organises SKAC Entrepreneurship Week - Halizan, Mohmood (2021)
KUANTAN, 8 October 2021 – The Sekolah Kebangsaan Assunta Convent Entrepreneurship Week 2021 (MK SKAC) collaboratively organised by SKAC Co-curriculum Unit and Parents and Teachers Association (PTA) and Centre for Industry and Community Network (ICoN), Graduate Development Department, Universiti Malaysia Pahang (UMP) held online has attracted the participation of 71 school students recently.